Space-based far-infrared interferometry technology development through a laboratory-based spatial/spectral interferometry testbed instrument - Locke D. Spencer; David A. Naylor; Savini, Giorgio; Peter A. R. Ade; Brad G. Gom (Proc. SPIE, 2014)
We describe recent progress in the development of a lab-based spatial/spectral double Fourier interferometer within the Astronomical Instrumentation Group (AIG) laboratories at the University of Lethbridge, Canada (UL). This testbed interferometer is used in the development of spatial/spectral interferometry observation, data processing, characterization, and analysis techniques in the Far-Infrared (FIR) region of the electromagnetic spectrum. Several interferometry technological development milestones on the FIR astrophysics roadmap are addressed by this ongoing research program of the UL AIG, all of which are needed as precursors to an eventual space-based FIR interferometry mission. This research program is supported by recent CRC, CFI, and NSERC grants.